Composite cutting tool and method of manufacturing and use thereof
Patent Information
- Application Number
- CN202611403940.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-09
AI Technical Summary
传统涂层高温抗氧化隔热性能不足,宽温域内硬度稳定性较差,切削过程中易遭受磨粒、扩散、粘结多重磨损
Smart Images

Figure CN122879674A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of surface protective coating technology, specifically relating to composite cutting tools, their preparation methods, and applications. Background Technology
[0002] For general machining applications involving milling, grooving, cutting, and drilling of carbon steel, alloy steel, and stainless steel, existing tool coatings still have several shortcomings. Traditional coatings lack sufficient high-temperature oxidation resistance and thermal insulation, exhibit poor hardness stability over a wide temperature range, and are susceptible to multiple wear processes including abrasive, diffusion, and adhesive wear during cutting. Furthermore, their high coefficient of friction and insufficient chemical inertness lead to built-up edge formation when machining carbon steel and chip adhesion and entanglement when machining stainless steel, making them unable to resist tool wear caused by work hardening. Moreover, conventional coatings have limited film-substrate adhesion and poor toughness, making them prone to cracking and peeling under alternating cutting loads. A single coating cannot achieve synergistic improvements in multiple properties, failing to meet the stringent requirements of multi-material machining. Therefore, tool improvements are still needed. Summary of the Invention
[0003] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, this invention proposes a composite cutting tool with high hardness, high wear resistance, high oxidation resistance, high toughness, and high bonding strength, as well as its preparation method and applications.
[0004] A first aspect of this application provides a composite cutting tool, comprising: A tool substrate and a functional coating disposed on the surface of the tool substrate, the functional coating comprising: A first coating is applied to the surface of the tool substrate; The second coating includes at least one stacked sub-coating, each sub-coating including a first sub-coating and a second sub-coating, the first sub-coating being disposed close to the first coating; A third coating is disposed on the surface of the second sub-coating away from the tool substrate; Wherein, the first coating and the first sub-coating each independently include Al a Ti 1-a N, 0.70≤a≤0.85; The second sub-coating includes Ti 1-x Nb x N, 0.10≤x≤0.30; The third coating includes Al z Ti 1-y-z Nb y N, 0.05≤y≤0.10, 0.70≤z≤0.85.
[0005] The composite coating system of this application achieves comprehensive performance far exceeding that of a single coating or simple superimposed coating through the following synergistic mechanism: First coating Al a Ti 1-a N utilizes its high Al content to impart excellent high-temperature oxidation resistance. At high temperatures, Al preferentially oxidizes to form a dense Al₂O₃ protective film, while also exhibiting good wear resistance and toughness. The second coating uses Al… a Ti 1-a N and Ti 1-x Nb x The multilayer structure formed by N, due to the significant differences in elastic modulus and lattice constants between the two layers, creates a large number of coherent or semi-coherent heterogeneous interfaces. Under intermittent cutting impact loads, the microcracks that initiate repeatedly deflect and bifurcate when encountering interlayer interfaces during propagation, significantly extending the crack propagation path and efficiently dissipating fracture energy, thereby significantly improving the overall toughness of the functional coating. Simultaneously, the introduction of Nb in the second sub-coating improves its chemical inertness and reduces its chemical affinity with Ni and Cr elements in the workpiece, effectively suppressing weld adhesion and built-up edge. In the third coating, Al... z Ti 1-y-z Nb y N combines high hardness, excellent high-temperature oxidation resistance (high Al content z≥0.70) and low friction coefficient. Nb atoms play a role in substitution solid solution strengthening, high Al content ensures high-temperature oxidation resistance, and Nb2O5 generated by Nb oxidation at high cutting temperatures has a self-lubricating effect. The above three layers gradually form a functional gradient structure from the tool matrix outward: "high wear resistance, high toughness bottom layer → high toughness middle layer → high wear resistance and anti-adhesion top layer", thus obtaining a composite tool with high hardness, high wear resistance, high oxidation resistance, high toughness and higher bonding strength.
[0006] According to an embodiment of this application, the number of sub-coatings is 1 to 10.
[0007] According to embodiments of this application, the composite cutting tool described above satisfies at least one of the following conditions: The first coating is a columnar NaCl-type face-centered cubic crystal structure; The thickness of the first coating is 1μm~3μm; The thickness ratio n of a single first sub-coating and a single second sub-coating satisfies 1 ≤ n ≤ 3; The total thickness of the second coating is 3μm~6μm; The third coating has an equiaxed crystal structure; The thickness of the third coating is 1μm to 3μm.
[0008] According to an embodiment of this application, the functional coating further includes a bonding layer disposed between the tool substrate and the first coating.
[0009] According to embodiments of this application, the composite cutting tool described above satisfies at least one of the following conditions: The bonding layer is made of at least one of TiN and Ti; The thickness of the bonding layer is 0.1 μm to 1.0 μm.
[0010] According to an embodiment of this application, the functional coating further includes a surface layer disposed on the surface of the third coating away from the tool substrate.
[0011] According to embodiments of this application, the composite cutting tool described above satisfies at least one of the following conditions: The surface layer is made of at least one of TiN, TiAlN, NbN, and TiNbN; The thickness of the surface layer is 1.0 μm to 2.0 μm.
[0012] According to embodiments of this application, the composite cutting tool described above satisfies at least one of the following conditions: The total thickness of the functional coating is 6μm~15μm; The hardness of the functional coating is ≥35 GPa.
[0013] According to embodiments of this application, the composite cutting tool described above satisfies at least one of the following conditions: The first coating does not contain Nb. Within the first sub-coating, and in a thickness region of 0 nm to 100 nm at a distance from the surface of the first sub-coating to the surface of the second sub-coating, the atomic percentage of Nb is 1 at% to 3 at, based on the total number of Al, Ti, and Nb atoms in the 0 nm to 100 nm thickness region.
[0014] A second aspect of this application provides a method for preparing the composite cutting tool described in the first aspect, comprising: Provide tool base; The first reaction is carried out in a reaction atmosphere of H2, AlCl3, TiCl4 and NH3 to form a first coating on one side surface of the tool substrate, thereby obtaining a first intermediate product; The second reaction is carried out in a reaction atmosphere of H2, AlCl3, TiCl4, and NH3 to form a first sub-coating on the surface of the first intermediate product, thereby obtaining the second intermediate product. The third reaction is carried out in a reaction atmosphere of H2, TiCl4, NbCl4, and NH3, forming a second sub-coating on the surface of the second intermediate product to obtain the third intermediate product; A fourth reaction is carried out in a reaction atmosphere of H2, AlCl3, TiCl4, NbCl4 and NH3 to form a third coating on the surface of the third intermediate product, thereby obtaining the composite tool; The first sub-coating and the second sub-coating constitute the second coating.
[0015] The above method is more conducive to promoting the mutual diffusion of elements between the first coating and the tool substrate, thereby forming a metallurgical bond and obtaining a functional coating with higher bonding strength.
[0016] According to an embodiment of this application, the second reaction and the third reaction are performed alternately m times, where 1 ≤ m ≤ 10 and m is a positive integer.
[0017] According to embodiments of this application, the above method satisfies at least one of the following conditions: The temperature of the first reaction is 750℃~850℃; The pressure of the first reaction is 5 mbar to 100 mbar; The first reaction time is 30 min to 90 min; The temperature of the second reaction is 750℃~850℃; The pressure of the second reaction is 5 mbar to 100 mbar, preferably 5 mbar to 20 mbar; The second reaction time is 6 min to 180 min; The temperature of the third reaction is 750℃~850℃; The pressure of the third reaction is 5 mbar to 100 mbar, preferably 5 mbar to 20 mbar; The third reaction time is 3 min to 120 min; The temperature of the fourth reaction is 750℃~850℃; The pressure of the fourth reaction is 5 mbar to 100 mbar; The fourth reaction time is 60 min to 180 min.
[0018] According to an embodiment of this application, the above method further includes: forming a bonding layer on the surface of the tool substrate under conditions of a temperature of 800°C to 900°C and a pressure of 50 mbar to 200 mbar.
[0019] According to an embodiment of this application, the above method further includes: forming a surface layer on the surface of the third coating under conditions of a temperature of 750°C to 1000°C and a pressure of 5 mbar to 200 mbar.
[0020] A third aspect of this application proposes the application of the coated composite tool described in the first aspect in milling, grooving and / or drilling of carbon steel, alloy steel and / or stainless steel materials. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the structure of a composite cutting tool according to an embodiment of this application.
[0022] Figure 2 This is a schematic diagram of the structure of a composite cutting tool according to another embodiment of this application.
[0023] Reference numerals: 100-Tool substrate; 200-Functional coating; 201-Bonding layer; 202-First coating; 203-First sub-coating; 204-Second sub-coating; 205-Second coating; 206-Third coating; 207-Surface layer. Detailed Implementation
[0024] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0025] In milling of carbon steel, alloy steel, and stainless steel, composite cutting tools are subjected to continuous alternating mechanical impacts and thermal cycles, making them prone to coating thermal cracking and micro-chipping of the cutting edge. Low-carbon steel has high plasticity and large cutting deformation, making it extremely easy to generate built-up edge that scratches the workpiece; medium and high-carbon steel is prone to crater wear and thermal fatigue. Alloy steel has poor thermal conductivity, and cutting temperatures can reach 900℃~1200℃. The hard carbides inside cause severe abrasive wear, and at high temperatures, Cr and Mo elements easily diffuse and corrode the composite cutting tool. Stainless steel has a prominent work hardening effect, strong affinity for Ni and Cr, serious chip entanglement problems, and high cutting resistance that easily induces vibration. The superposition of these three materials in milling impact conditions will simultaneously exacerbate adhesive, abrasive, and diffusion wear. Composite cutting tools have a fast passivation rate, and it is difficult to guarantee dimensional stability and surface quality. Composite cutting tool coatings are required to have high-temperature oxidation resistance and thermal insulation capabilities above 1100℃, high hardness at high and low temperatures to resist various types of wear; low friction and strong chemical inertness to suppress built-up edge; high bonding strength and sufficient toughness to withstand the thermal shock of milling.
[0026] In the grooving and cutting of carbon steel, alloy steel, and stainless steel, composite tools suffer from narrow cutting zones, poor chip removal, and three-sided friction and vibration during machining. Carbon steel is prone to built-up edge adhesion; alloy steel experiences high-temperature, high-abrasive wear and is susceptible to diffuse corrosion; stainless steel suffers from severe work hardening, prominent weld beads, and tool deformation at the cut end, resulting in uneven wear on the composite tool edge and difficulty in maintaining stable dimensional accuracy. Therefore, composite tools require coatings with low friction coefficients and strong chemical inertness to inhibit built-up edge adhesion to the metal; excellent high-temperature oxidation resistance and thermal insulation to resist abrasive and diffuse wear; and high bonding strength and toughness to withstand cutting vibration and alternating loads.
[0027] In the drilling of carbon steel, alloy steel, and stainless steel, heat dissipation and chip removal space are limited, and axial cutting resistance is high. Low-carbon steel chips are long and easily entangle the drill bit, resulting in built-up edge; alloy steel has poor thermal conductivity, leading to severe high temperatures at the drill tip, and hard particles exacerbate abrasive wear at the outer edge corners; stainless steel exhibits significant work hardening, and severe metal adhesion can easily scratch the hole wall, resulting in common problems such as chip blockage, rapid drill bit dulling, and poor hole dimensions and surface finish. Composite tool coatings are required to possess excellent high-temperature thermal insulation and oxidation resistance to reduce the thermal load on the drill tip; low friction and high chemical inertness to prevent chip adhesion and entanglement and inhibit built-up edge; high hardness at high and low temperatures to resist abrasive and diffusion wear at the outer edge; and high film-substrate adhesion and good toughness to withstand continuous axial cutting loads.
[0028] In summary, for general machining operations involving milling, grooving, cutting, and drilling of carbon steel, alloy steel, and stainless steel, composite tool coatings are required to possess high-temperature oxidation resistance and heat insulation capabilities, high hardness at both high and low temperatures, and resistance to multiple wear processes including abrasive, diffusion, and adhesive wear; low coefficient of friction and strong chemical inertness to inhibit built-up edge on carbon steel, weld entanglement on stainless steel, and work-hardening wear; and high coating-substrate adhesion and excellent toughness. Therefore, the industry urgently needs a coating solution that combines high hardness, high wear resistance, high oxidation resistance, high toughness, and even higher bonding strength.
[0029] Based on the above, the first aspect of this application proposes a composite cutting tool, referring to... Figure 1 The composite tool includes: The tool substrate 100 and the functional coating 200 disposed on the surface of the tool substrate 100, the functional coating 200 comprising: A first coating 202 is applied to the surface of the tool substrate 100; The second coating 205 includes at least one stacked sub-coatings, each sub-coating including a first sub-coating 203 and a second sub-coating 204, wherein the first sub-coating 203 is disposed close to the first coating 202; The third coating 206 is disposed on the surface of the second sub-coating 204 away from the tool substrate 100; Wherein, the first coating 202 and the first sub-coating 203 each independently include Al a Ti 1-a N, 0.70≤a≤0.85; The second sub-coating 204 includes Ti 1-x Nb x N, 0.10≤x≤0.30; The third coating 206 includes Al z Ti 1-y-z Nb y N, 0.05≤y≤0.10, 0.70≤z≤0.85.
[0030] The composite coating system of this application achieves comprehensive performance far exceeding that of a single coating or simple superimposed coating through the following synergistic mechanism: First coating Al a Ti 1-a N utilizes its high Al content to impart excellent high-temperature oxidation resistance. At high temperatures, Al preferentially oxidizes to form a dense Al₂O₃ protective film, while also exhibiting good wear resistance and toughness. The second coating uses Al… a Ti 1-a N and Ti 1-x Nb x The multilayer structure formed by N, due to the significant differences in elastic modulus and lattice constants between the two layers, creates a large number of coherent or semi-coherent heterogeneous interfaces. Under intermittent cutting impact loads, the microcracks that initiate repeatedly deflect and bifurcate when encountering interlayer interfaces during propagation, significantly extending the crack propagation path and efficiently dissipating fracture energy, thereby significantly improving the overall toughness of the functional coating. Simultaneously, the introduction of Nb in the second sub-coating improves its chemical inertness and reduces its chemical affinity with Ni and Cr elements in the workpiece, effectively suppressing weld adhesion and built-up edge. In the third coating, Al... z Ti 1-y-z Nb y N combines high hardness, excellent high-temperature oxidation resistance (high Al content z≥0.70) and low friction coefficient. Nb atoms play a role in substitution solid solution strengthening, high Al content ensures high-temperature oxidation resistance, and Nb2O5 generated by Nb oxidation at high cutting temperatures has a self-lubricating effect. The above three layers gradually form a functional gradient structure from the tool matrix outward: "high wear resistance, high toughness bottom layer → high toughness middle layer → high wear resistance and anti-adhesion top layer", thus obtaining a composite tool with high hardness, high wear resistance, high oxidation resistance, high toughness and higher bonding strength.
[0031] When a < 0.70, the Al content in the first coating and / or the first sub-coating is low, which may lead to insufficient high-temperature oxidation resistance; when a > 0.85, the first coating and / or the first sub-coating are prone to precipitate hexagonal fibrous mineral-type low-hardness AlN phase (h-AlN), which may lead to a sharp decrease in coating hardness and wear resistance.
[0032] When x < 0.10, the Nb content is too low, and the hardness and anti-sticking effect of the second sub-coating may be insufficient; when x > 0.30, excessive Nb may lead to high hardness but insufficient toughness of the second sub-coating.
[0033] When y < 0.05, the Nb content is too low, which may result in insufficient hardness, wear resistance and anti-sticking effect of the third coating; when y > 0.10, the Nb content is too high, which may result in low toughness of the third coating.
[0034] When z < 0.70, the low Al content may lead to insufficient high-temperature oxidation resistance of the third coating; when z > 0.85, hexagonal AlN phase is easily precipitated, which may lead to a decrease in the hardness and wear resistance of the third coating.
[0035] According to embodiments of this application, the material of the tool substrate 100 includes at least one of cemented carbide, cermet, alumina-based ceramic, SiAlON ceramic, silicon nitride-based ceramic, cubic boron nitride, polycrystalline diamond, and high-speed steel. These materials possess high hardness, high bending strength, and good high-temperature structural stability, providing stable mechanical support for the functional coating, reducing coating failure caused by plastic deformation of the tool substrate, and exhibiting good interfacial compatibility with the functional coating, thus ensuring bonding strength.
[0036] According to embodiments of this application, the number of sub-coatings is 1 to 10. The periodic alternation design of the first and second sub-coatings increases the number density of heterogeneous interfaces. In interrupted cutting, impact microcracks deflect and bifurcate when they encounter interlayer interfaces, preventing them from directly penetrating the entire functional coating to reach the tool substrate, thereby significantly improving the toughness of the functional coating. With a fixed total thickness of the second coating, when the number of sub-coatings is greater than 10, the single-layer thickness of each first and second sub-coating is too low (<0.3 μm). Crystals may have just completed nucleation but have not yet fully grown before entering the deposition of another layer, ultimately potentially leading to a decrease in the overall crystallinity of the functional coating, which in turn weakens its hardness and wear resistance.
[0037] According to an embodiment of this application, the first coating is a columnar NaCl-type face-centered cubic crystal structure. This crystal structure has a regular lattice arrangement and high structural stability, which can effectively improve the overall density and structural strength of the first coating, enhance the load transfer capacity inside the first coating, significantly improve the wear resistance and high-temperature structural stability of the first coating, and adapt to the alternating loads and high-temperature conditions during the cutting process.
[0038] According to embodiments of this application, the thickness of the first coating 202 is 1 μm to 3 μm; specifically, it is 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, or any two of these ranges. Within this range, the first coating can fully utilize the high-temperature oxidation resistance advantages brought by the high aluminum component, forming a stable and dense protective underlayer, effectively improving the basic wear resistance and toughness of the first coating, while ensuring good interfacial compatibility between the first coating and the second coating, and enhancing the overall film bonding stability.
[0039] According to an embodiment of this application, the first coating 202 does not contain Nb. The undetectable presence of Nb in the first coating ensures its high toughness.
[0040] According to an embodiment of this application, the thickness ratio n of a single first sub-coating 203 and a single second sub-coating 204 satisfies 1 ≤ n ≤ 3. As a specific example, the thickness ratio n of a single first sub-coating and a single second sub-coating can be 1, 1.3, 1.5, 1.8, 2, 2.3, 2.5, 2.8, 3, or any two of these ranges. Within the above range, due to the NbN solid solution strengthening effect, the second sub-coating (Ti 1-x Nb x The hardness of N is significantly higher than that of the first sub-coating (Al). a Ti 1-a When n < 1, the thickness of the second sub-coating is too high, and the second coating may be too hard and lack toughness; when n > 3, the thickness of the second sub-coating is too small, and the second coating may be too soft and lack wear resistance.
[0041] According to an embodiment of this application, within the first sub-coating 203 and in a thickness region of 0 nm to 100 nm at a distance from the surface of the first sub-coating 203 near the second sub-coating 204, the atomic percentage content of Nb is 1 at% to 3 at% based on the total number of Al, Ti, and Nb atoms in the 0 nm to 100 nm thickness region. Specifically, it is 1 at%, 1.5 at%, 2 at%, 2.5 at%, 3 at%, or any two of these ranges. Within this range, the large internal stress that may be caused by a sudden change in composition at the interface between the first and second sub-coating layers is avoided or reduced, thus significantly improving the interlayer bonding strength.
[0042] Specifically, the atomic percentage of Nb gradually decreases in the thickness direction away from the second sub-coating 204. The atomic percentage of Nb is the volume average content within this thickness region, not the elemental content at a single surface location. This elemental content can be obtained through EDS (energy-dispersive X-ray spectroscopy) testing.
[0043] According to embodiments of this application, the total thickness of the second coating 205 is 3μm to 6μm, specifically 3μm, 4μm, 5μm, 6μm, or any two of these ranges. Within this range, the overall impact toughness and fatigue resistance of the second coating are enhanced, while ensuring excellent structural density and wear resistance, making it suitable for intermittent cutting and impact cutting conditions.
[0044] According to an embodiment of this application, the third coating 206 has an equiaxed crystal structure; the isotropic characteristics of the equiaxed crystal structure are beneficial for uniformly dispersing cutting stress and avoiding or reducing preferential oxidation and corrosion along columnar grain boundaries.
[0045] According to an embodiment of this application, the third coating 206 contains Nb, which has high wear resistance and anti-stick properties, and steadily improves the high-temperature service performance of the coating.
[0046] According to embodiments of this application, the thickness of the third coating 206 is 1μm to 3μm, specifically within the range of 1μm, 1.5μm, 2μm, 2.5μm, 3μm, or any two thereof. Within this range, the third coating can fully utilize the advantages of high aluminum oxidation resistance, niobium oxide self-lubrication, and solid solution strengthening, effectively improving the overall wear resistance, anti-sticking, and high-temperature resistance of the composite tool surface, while ensuring the overall structural matching and dimensional stability of the functional coating.
[0047] According to the embodiments of this application, referring to Figure 2 The functional coating 200 further includes a bonding layer 201, which is disposed between the tool substrate 100 and the first coating 202. The bonding layer can effectively improve the interface compatibility between the tool substrate and the functional coating, increase the bonding strength between the two, enhance the metallurgical bonding effect between the functional coating and the tool substrate, improve the overall adhesion stability of the functional coating, and effectively improve the anti-stripping ability of the composite tool under impact and high-temperature cutting conditions.
[0048] According to embodiments of this application, the bonding layer 201 is made of at least one of TiN and Ti. These materials exhibit excellent compatibility with various tool substrates, effectively improving interfacial wettability and bonding performance, mitigating the property differences between the tool substrate and the functional coating, and stabilizing the overall structural strength of the functional coating.
[0049] According to embodiments of this application, the thickness of the bonding layer 201 is 0.1 μm to 1.0 μm, specifically within the range of 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1.0 μm, or any two thereof. Within this range, the bonding layer can fully utilize its interfacial transition and adhesion enhancement effects, effectively improving the bonding strength between the tool substrate and the functional coating, while not introducing additional internal stress, ensuring the overall stability of the functional coating structure.
[0050] According to the embodiments of this application, referring to Figure 2 The functional coating further includes a surface layer 207, which is disposed on the surface of the third coating 206 away from the tool substrate 100. The surface layer can directly withstand cutting friction, high-temperature oxidation, and workpiece adhesion, effectively improving the wear resistance, anti-adhesion, and high-temperature oxidation resistance of the composite tool surface, and protecting the structural stability of the inner functional coating.
[0051] According to embodiments of this application, the material of the surface layer 207 includes at least one of TiN, TiAlN, NbN, and TiNbN. These materials exhibit high chemical inertness, low coefficient of friction, and excellent high-temperature stability, effectively improving the composite cutting tool's resistance to built-up edge and weld adhesion, enhancing the cutting surface quality, and improving the high-temperature wear resistance and oxidation resistance of the composite cutting tool.
[0052] According to embodiments of this application, the thickness of the surface layer 207 is 1.0 μm to 2.0 μm, specifically within the range of 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, or any two of these ranges. Within this range, the surface layer can form a uniform and complete protective film, fully leveraging its protective advantages of low friction, high inertness, and high temperature resistance, effectively improving the cutting stability and service life of composite tools.
[0053] According to embodiments of this application, the total thickness of the functional coating 200 is 6μm to 15μm, specifically within the range of 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, or any two of these ranges. Within this range, the multi-layer gradient structure can synergistically leverage the combined advantages of wear resistance, toughening, oxidation resistance, and anti-adhesion, effectively improving the overall cutting performance of the composite tool, ensuring a dense and stable functional coating structure, reasonable mechanical property matching, and adaptability to various material and multi-process machining conditions.
[0054] According to an embodiment of this application, the hardness of the functional coating 200 is ≥35 GPa. Within the above range, the functional coating of this application has high hardness, which can effectively improve the composite tool's resistance to abrasive wear and cutting extrusion wear, and significantly improve the wear resistance and machining stability of the composite tool.
[0055] Currently, physical vapor deposition (PVD) coating composite tools are widely used in machining with existing coated materials. Common coating systems include nitride-based single-layer or multi-layer coatings. These PVD coatings typically have the advantage of high hardness, but to achieve this high hardness, significant compressive stress usually accumulates within the coating. This high-stress state often leads to a decrease in the bonding strength between the coating and the tool substrate. Under the high temperature and high mechanical load conditions required for high-speed cutting, insufficient coating bonding strength directly results in premature coating peeling failure, shortening the life of the composite tool. Because the deposition temperature of the PVD process is relatively low (usually below 700℃), the bonding between the coating and the tool substrate, as well as between the coating layers, is mainly mechanical. Although this can be improved to some extent through process control, further improvement of its bonding strength faces bottlenecks. In contrast, the deposition temperature of the chemical vapor deposition (CVD) process is higher (usually between 700℃ and 1050℃), which is more conducive to promoting the interdiffusion of elements between the coating and the tool substrate, thereby forming a metallurgical bond and obtaining a functional coating with higher bonding strength.
[0056] A second aspect of this application provides a method for preparing the composite cutting tool described in the first aspect, comprising: S10: Provides the tool base.
[0057] S20: A first reaction is carried out in a reaction atmosphere of H2, AlCl3, TiCl4 and NH3 to form a first coating on one side surface of the tool substrate, thereby obtaining a first intermediate product.
[0058] In this step, H2 acts as a reducing carrier gas, providing a stable reducing atmosphere for the reaction system and inhibiting the oxidative decomposition of precursor gases such as AlCl3, TiCl4, and NH3. The AlCl3 and TiCl4 metal halide precursors undergo a gas-phase chemical reaction with the NH3 nitrogen source on the tool substrate surface, generating high-alumina Al in situ. a Ti 1-a Nitrogen solid solution deposits are uniformly deposited on the surface of the tool substrate and continuously grow to form a dense, non-porous columnar NaCl-type face-centered cubic first coating.
[0059] According to embodiments of this application, the temperature of the first reaction is 750℃~850℃, specifically 750℃, 770℃, 790℃, 800℃, 810℃, 830℃, 850℃, or any range between two of these. Within this range, the chemical reactivity of the precursor gas can be fully activated, ensuring uniform co-deposition of Al and Ti elements, improving the crystal integrity and density of the first coating, stabilizing the formation of a regular columnar crystal structure, and effectively matching the temperature tolerance of the tool substrate, ensuring bonding performance, and significantly improving the wear resistance and high-temperature structural stability of the first coating.
[0060] According to embodiments of this application, the pressure of the first reaction is 5 mbar to 100 mbar, specifically within the range of 5 mbar, 10 mbar, 15 mbar, 20 mbar, 30 mbar, 40 mbar, 50 mbar, 60 mbar, 70 mbar, 80 mbar, 90 mbar, 100 mbar, or any two of these ranges. Within this range, the concentration of precursor gas molecules and the gas-phase reaction rate can be precisely controlled, ensuring uniform growth of the first coating, improving its thickness consistency, and effectively enhancing the overall structural strength and interface compatibility of the first coating.
[0061] According to an embodiment of this application, the reaction time of the first reaction is 30 min to 90 min. Specifically, it is within the range of 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, or any two of these ranges. Within the above range, it is beneficial to form a dense first coating with a suitable thickness.
[0062] According to an embodiment of this application, before forming the first coating, the process further includes forming a bonding layer on the surface of the tool substrate under conditions of a temperature of 800℃~900℃, a pressure of 50mbar~200mbar, and a time of 6min~60min. Under these conditions, it is possible to ensure that the precursor gas of the bonding layer is fully and uniformly deposited on the surface of the tool substrate, improve the crystal quality and density of the bonding layer, strengthen the metallurgical bonding effect between the tool substrate and the bonding layer, effectively improve the bonding strength, alleviate the difference in physical properties between the tool substrate and the functional coating, ensure the stable adhesion of subsequent multilayer functional coatings, and significantly improve the composite tool's resistance to peeling and impact.
[0063] S30: A second reaction is carried out in a reaction atmosphere of H2, AlCl3, TiCl4, and NH3 to form a first sub-coating on the surface of the first intermediate product, thereby obtaining a second intermediate product.
[0064] The chemical reaction in the second step is consistent with the process of the first reaction, and will not be described in detail here. This step can generate Al with the same composition and structure as the first coating in situ. a Ti 1-aN ensures the bonding strength with the first coating.
[0065] According to embodiments of this application, the temperature of the second reaction is 750°C to 850°C, specifically 750°C, 770°C, 790°C, 800°C, 810°C, 830°C, 850°C, or any range between two of these. Within this range, stable vapor deposition reaction kinetics can be maintained continuously, ensuring the regular growth of the first sub-coating grains, improving the density and structural uniformity of the first sub-coating, enhancing the interlayer interface bonding strength, and providing excellent substrate conditions for subsequent deposition.
[0066] According to embodiments of this application, the pressure of the second reaction is 5 mbar to 100 mbar, specifically 5 mbar to 20 mbar. As a specific example, the pressure of the second reaction is within the range of 5 mbar, 10 mbar, 15 mbar, 20 mbar, 30 mbar, 40 mbar, 50 mbar, 60 mbar, 70 mbar, 80 mbar, 90 mbar, 100 mbar, or any two of these ranges. Within these ranges, the precursor gas diffuses uniformly, and the reaction rate is gradual and stable, effectively improving the thickness uniformity and surface smoothness of the first sub-coating, and enhancing structural stability.
[0067] According to embodiments of this application, the second reaction time is 6 min to 180 min. Specifically, it can be 6 min, 10 min, 30 min, 60 min, 90 min, 120 min, 150 min, 180 min, or any two of these ranges. Within these ranges, it is beneficial to form a dense first sub-coating with a suitable thickness.
[0068] S40: A third reaction is carried out in a reaction atmosphere of H2, TiCl4, NbCl4, and NH3 to form a second sub-coating on the surface of the second intermediate product, thereby obtaining a third intermediate product, wherein the first sub-coating and the second sub-coating constitute the second coating.
[0069] In this step, H2 maintains the reducing deposition environment of the system and inhibits the oxidative failure of the precursor gas; TiCl4, NbCl4, and NH3 undergo a high-temperature gas-phase reaction to generate Ti in situ. 1-x Nb x The N solid solution coating is uniformly deposited on the surface of the first sub-coating to form a heterogeneous interlayer interface, while simultaneously achieving gradient diffusion of trace Nb elements at the interface, effectively improving the interlayer stress state.
[0070] According to embodiments of this application, the temperature of the third reaction is 750℃~850℃, specifically 750℃, 770℃, 790℃, 800℃, 810℃, 830℃, 850℃, or any range between two of these. Within this temperature range, the co-deposition reaction of Ti and Nb precursor gases can be fully activated, ensuring that Nb elements are uniformly dissolved in the TiN lattice, fully utilizing the solid solution strengthening effect, improving the hardness and chemical inertness of the second sub-coating, while ensuring tight interlayer bonding and enhancing the overall toughness of the second coating structure.
[0071] According to embodiments of this application, the pressure of the third reaction is 5 mbar to 100 mbar, specifically 5 mbar to 20 mbar. As a specific example, the pressure of the third reaction is within the range of 5 mbar, 10 mbar, 15 mbar, 20 mbar, 30 mbar, 40 mbar, 50 mbar, 60 mbar, 70 mbar, 80 mbar, 90 mbar, 100 mbar, or any two of these ranges. Within these ranges, the co-deposition ratio of Ti and Nb elements can be precisely controlled, the target composition ratio can be stably achieved, the compositional uniformity and structural density of the second sub-coating can be improved, sufficient coherent / semi-coherent heterogeneous interfaces can be formed, and the impact toughening effect of the second coating can be effectively enhanced.
[0072] According to embodiments of this application, the time for the third reaction is 3 to 120 minutes. Specifically, it can be 3 minutes, 10 minutes, 30 minutes, 60 minutes, 90 minutes, 120 minutes, or any two of these ranges. Within these ranges, it is beneficial to form a dense second sub-coating with a suitable thickness.
[0073] S50: A fourth reaction is carried out in a reaction atmosphere of H2, AlCl3, TiCl4, NbCl4 and NH3 to form a third coating on the surface of the third intermediate product, thereby obtaining the composite tool.
[0074] In this step, the precursor gases (AlCl3, TiCl4, NbCl4, and NH3) undergo a simultaneous vapor-phase co-deposition reaction with NH3 under a reducing H2 atmosphere, resulting in the uniform solid-solution bonding of Al, Ti, and Nb metals, and the in-situ formation of Al. z Ti 1-y-z Nb y The N-based multi-nitride solid solution coating is uniformly applied to the surface of the second sub-coating, forming an isotropic equiaxed crystal structure that combines high hardness, high-temperature oxidation resistance, and self-lubricating properties.
[0075] According to embodiments of this application, the temperature of the fourth reaction is 750℃~850℃, specifically 750℃, 770℃, 790℃, 800℃, 810℃, 830℃, 850℃, or any range between two of these. Within this range, uniform co-doping solid solution of metal elements can be ensured, improving the uniformity of Nb element distribution in the third coating, fully utilizing the substitution solid solution strengthening effect, and simultaneously ensuring stable film formation of the high Al composition.
[0076] According to embodiments of this application, the pressure of the fourth reaction is 5 mbar to 100 mbar, specifically within the range of 5 mbar, 10 mbar, 15 mbar, 20 mbar, 30 mbar, 40 mbar, 50 mbar, 60 mbar, 70 mbar, 80 mbar, 90 mbar, 100 mbar, or any two of these ranges. Within this range, the reaction rate and deposition efficiency of the multi-component precursor gas can be stably controlled, ensuring uniform thickness of the third coating.
[0077] According to embodiments of this application, the fourth reaction time is 60 min to 180 min. Specifically, it is within the range of 60 min, 90 min, 120 min, 150 min, 180 min, or any two of these ranges. Within this range, it is beneficial to form a dense third coating of suitable thickness.
[0078] According to the embodiments of this application, the purity of the reaction gases such as H2, AlCl3, TiCl4, NH3, and NbCl4 used in this application is not less than 99.99% (volume fraction).
[0079] According to an embodiment of this application, after forming the third coating, the method further includes: forming a surface layer on the surface of the third coating under conditions of a temperature of 750°C to 1000°C, a pressure of 5 mbar to 200 mbar, and a time of 40 min to 120 min. Under these conditions, uniform and dense growth of the surface layer material can be ensured, improving the integrity of the surface layer structure.
[0080] A third aspect of this application provides the application of the composite tool described in the first aspect in milling, grooving and / or drilling of carbon steel, alloy steel and / or stainless steel materials.
[0081] The embodiments of this application are described in detail below.
[0082] Example 1 A composite cutting tool, wherein the tool substrate 100 is a WC-Co based cemented carbide, the bonding layer 201 is TiN, and the first coating layer 202 is Al. 0.70 Ti 0.30 N, the second coating 205 is the first sub-coating 203 (Al) 0.70 Ti0.30 N) and second sub-coating 204 (Ti) 0.9 Nb 0.1 An alternation of N), the third coating 206 is Al 0.70 Ti 0.25 Nb 0.05 N, the surface layer 207 is TiN. Its preparation method is as follows: (1) At a temperature of 850℃ and a pressure of 100mbar, H2, TiCl4 and N2 with a purity greater than 99.99% were used to deposit a bonding layer 201 on the surface of the tool substrate 100 by chemical vapor deposition. The deposition time was 120min and the thickness of the bonding layer 201 was 0.5μm. (2) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit the first coating 202 on the surface of the bonding layer 201 by chemical vapor deposition. The deposition time was 60min and the thickness of the first coating 202 was 1.5μm. (3) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a first sub-coating 203 on the surface of the first coating 202 by chemical vapor deposition. The deposition time was 60min and the thickness of the first sub-coating 203 was 1.5μm. At a temperature of 800℃ and a pressure of 5mbar, H2, NbCl4, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a second sub-coating 204 on the surface of 203 by chemical vapor deposition. The deposition time was 60min and the thickness of the second sub-coating 204 was 1.5μm. (4) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4, NbCl4 and NH3 with a purity greater than 99.99% were used to deposit a third coating 206 on the surface of the second sub-coating 204 by chemical vapor deposition. The deposition time was 60min and the thickness of the third coating 206 was 1.5μm. (5) At a temperature of 800℃ and a pressure of 50mbar, H2, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a surface layer 207 on the surface of the third coating 206 by chemical vapor deposition. The deposition time was 90min and the thickness of the surface layer 207 was 1.0μm.
[0083] Example 2 A composite cutting tool, wherein the tool substrate 100 is a WC-Co based cemented carbide, the bonding layer 201 is TiN, and the first coating layer 202 is Al. 0.80 Ti 0.20 N, the second coating 205 is the first sub-coating 203 (Al)0.80 Ti 0.20 N) and second sub-coating 204 (Ti) 0.8 Nb 0.2 An alternation of N), the third coating 206 is Al 0.80 Ti 0.12 Nb 0.08 N, the surface layer 207 is TiN. Its preparation method is as follows: (1) At a temperature of 850℃ and a pressure of 100mbar, H2, TiCl4 and N2 with a purity greater than 99.99% were used to deposit a bonding layer 201 on the surface of the tool substrate 100 by chemical vapor deposition. The deposition time was 120min and the thickness of the bonding layer 201 was 0.5μm. (2) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit the first coating 202 on the surface of the bonding layer 201 by chemical vapor deposition. The deposition time was 60min and the thickness of the first coating 202 was 1.5μm. (3) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a first sub-coating 203 on the surface of the first coating 202 by chemical vapor deposition. The deposition time was 60min and the thickness of the first sub-coating 203 was 1.5μm. At a temperature of 800℃ and a pressure of 5mbar, H2, NbCl4, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a second sub-coating 204 on the surface of the first sub-coating 203 by chemical vapor deposition. The deposition time was 60min and the thickness of 204 was 1.5μm. (4) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4, NbCl4 and NH3 with a purity greater than 99.99% were used to deposit a third coating 206 on the surface of the second sub-coating 204 by chemical vapor deposition. The deposition time was 60min and the thickness of the third coating 206 was 1.5μm. (5) At a temperature of 800℃ and a pressure of 50mbar, H2, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a surface layer 207 on the surface of the third coating 206 by chemical vapor deposition. The deposition time was 90min and the thickness of the surface layer 207 was 1.0μm.
[0084] Example 3 A composite cutting tool, wherein the tool substrate 100 is a WC-Co based cemented carbide, the bonding layer 201 is TiN, and the first coating layer 202 is Al. 0.85 Ti 0.15N, the second coating 205 is the first sub-coating 203 (Al) 0.85 Ti 0.15 N) and second sub-coating 204 (Ti) 0.7 Nb 0.3 An alternation of N), the third coating 206 is Al 0.85 Ti 0.05 Nb 0.10 N, the surface layer 207 is TiN. Its preparation method is as follows: (1) At a temperature of 850℃ and a pressure of 100mbar, H2, TiCl4 and N2 with a purity greater than 99.99% were used to deposit a bonding layer 201 on the surface of the tool substrate 100 by chemical vapor deposition. The deposition time was 120min and the thickness of the bonding layer 201 was 0.5μm. (2) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit the first coating 202 on the surface of the bonding layer 201 by chemical vapor deposition. The deposition time was 60min and the thickness of the first coating 202 was 1.5μm. (3) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a first sub-coating 203 on the surface of the first coating 202 by chemical vapor deposition. The deposition time was 60min and the thickness of the first sub-coating 203 was 1.5μm. At a temperature of 800℃ and a pressure of 5mbar, H2, NbCl4, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a second sub-coating 204 on the surface of the first sub-coating 203 by chemical vapor deposition. The deposition time was 60min and the thickness of the second sub-coating 204 was 1.5μm. (4) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4, NbCl4 and NH3 with a purity greater than 99.99% were used to deposit a third coating 206 on the surface of the second sub-coating 204 by chemical vapor deposition. The deposition time was 60min and the thickness of the third coating 206 was 1.5μm. (5) At a temperature of 800℃ and a pressure of 50mbar, H2, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a surface layer 207 on the surface of the third coating 206 by chemical vapor deposition. The deposition time was 90min and the thickness of the surface layer 207 was 1.0μm.
[0085] Example 4 A composite cutting tool, wherein the tool substrate 100 is a WC-Co based cemented carbide, the bonding layer 201 is TiN, and the first coating layer 202 is Al. 0.80Ti 0.20 N, the second coating 205 is the first sub-coating 203 (Al) 0.80 Ti 0.20 N) and second sub-coating 204 (Ti) 0.8 Nb 0.2 The two alternations of N) and the third coating 206 are Al 0.80 Ti 0.12 Nb 0.08 N, the surface layer 207 is TiN. Its preparation method is as follows: (1) At a temperature of 850℃ and a pressure of 100mbar, H2, TiCl4 and N2 with a purity greater than 99.99% were used to deposit a bonding layer 201 on the surface of the tool substrate 100 by chemical vapor deposition. The deposition time was 120min and the thickness of the bonding layer 201 was 0.5μm. (2) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit the first coating 202 on the surface of the bonding layer 201 by chemical vapor deposition. The deposition time was 60min and the thickness of the first coating 202 was 1.5μm. (3) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a first sub-coating 203 on the surface of the first coating 202 by chemical vapor deposition. The deposition time was 30min and the thickness of 203 was 0.75μm. At a temperature of 800℃ and a pressure of 5mbar, H2, NbCl4, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a second sub-coating 204 on the surface of the first sub-coating 203 by chemical vapor deposition. The deposition time was 30min and the thickness of 204 was 0.75μm. The first sub-coating 203 and the second sub-coating 204 were deposited alternately twice to obtain a second coating 205 with a total thickness of 3.0μm. (4) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4, NbCl4 and NH3 with a purity greater than 99.99% were used to deposit a third coating 206 on the surface of the second sub-coating 204 by chemical vapor deposition. The deposition time was 60min and the thickness of the third coating 206 was 1.5μm. (5) At a temperature of 800℃ and a pressure of 50mbar, H2, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a surface layer 207 on the surface of the third coating 206 by chemical vapor deposition. The deposition time was 90min and the thickness of the surface layer 207 was 1.0μm.
[0086] Example 5 A composite cutting tool, wherein the tool substrate 100 is a WC-Co based cemented carbide, the bonding layer 201 is TiN, and the first coating layer 202 is Al. 0.80 Ti 0.20 N, the second coating 205 is the first sub-coating 203 (Al) 0.80 Ti 0.20 N) and second sub-coating 204 (Ti) 0.8 Nb 0.2 The ten alternations of N) and the third coating 206 are Al 0.80 Ti 0.12 Nb 0.08 N, the surface layer 207 is TiN. Its preparation method is as follows: (1) At a temperature of 850℃ and a pressure of 100mbar, H2, TiCl4 and N2 with a purity greater than 99.99% were used to deposit a bonding layer 201 on the surface of the tool substrate 100 by chemical vapor deposition. The deposition time was 120min and the thickness of the bonding layer 201 was 0.5μm. (2) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit the first coating 202 on the surface of the bonding layer 201 by chemical vapor deposition. The deposition time was 60min and the thickness of the first coating 202 was 1.5μm. (3) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a first sub-coating 203 on the surface of the first coating 202 by chemical vapor deposition. The deposition time was 6min and the thickness of 203 was 0.15μm. At a temperature of 800℃ and a pressure of 5mbar, H2, NbCl4, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a second sub-coating 204 on the surface of the first sub-coating 203 by chemical vapor deposition. The deposition time was 6min and the thickness of 204 was 0.15μm. The first sub-coating 203 and the second sub-coating 204 were deposited alternately ten times to obtain a second coating 205 with a total thickness of 3.0μm. (4) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4, NbCl4 and NH3 with a purity greater than 99.99% were used to deposit a third coating 206 on the surface of the second sub-coating 204 by chemical vapor deposition. The deposition time was 60min and the thickness of the third coating 206 was 1.5μm. (5) At a temperature of 800℃ and a pressure of 50mbar, H2, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a surface layer 207 on the surface of the third coating 206 by chemical vapor deposition. The deposition time was 90min and the thickness of the surface layer 207 was 1.0μm.
[0087] Example 6 A composite cutting tool, wherein the tool substrate 100 is a WC-Co based cemented carbide, the bonding layer 201 is TiN, and the first coating layer 202 is Al. 0.80 Ti 0.20 N, the second coating 205 is the first sub-coating 203 (Al) 0.80 Ti 0.20 N) and second sub-coating 204 (Ti) 0.8 Nb 0.2 An alternation of N), the third coating 206 is Al 0.80 Ti 0.12 Nb 0.08 N, the surface layer 207 is TiN. Its preparation method is as follows: (1) At a temperature of 850℃ and a pressure of 100mbar, H2, TiCl4 and N2 with a purity greater than 99.99% were used to deposit a bonding layer 201 on the surface of the tool substrate 100 by chemical vapor deposition. The deposition time was 120min and the thickness of the bonding layer 201 was 0.5μm. (2) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit the first coating 202 on the surface of the bonding layer 201 by chemical vapor deposition. The deposition time was 60min and the thickness of the first coating 202 was 1.5μm. (3) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a first sub-coating 203 on the surface of the first coating 202 by chemical vapor deposition. The deposition time was 85min and the thickness of the first sub-coating 203 was 2.1μm. At a temperature of 800℃ and a pressure of 5mbar, H2, NbCl4, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a second sub-coating 204 on the surface of the first sub-coating 203 by chemical vapor deposition. The deposition time was 30min and the thickness of 204 was 0.7μm. (4) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4, NbCl4 and NH3 with a purity greater than 99.99% were used to deposit a third coating 206 on the surface of the second sub-coating 204 by chemical vapor deposition. The deposition time was 60min and the thickness of the third coating 206 was 1.5μm. (5) At a temperature of 800℃ and a pressure of 50mbar, H2, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a surface layer 207 on the surface of the third coating 206 by chemical vapor deposition. The deposition time was 90min and the thickness of the surface layer 207 was 1.0μm.
[0088] Example 7 A composite cutting tool, wherein the tool substrate 100 is a WC-Co based cemented carbide, the bonding layer 201 is TiN, and the first coating layer 202 is Al. 0.80 Ti 0.20 N, the second coating 205 is the first sub-coating 203 (Al) 0.80 Ti 0.20 N) and second sub-coating 204 (Ti) 0.8 Nb 0.2 An alternation of N), the third coating 206 is Al 0.80 Ti 0.12 Nb 0.08 N, the surface layer 207 is TiN. Its preparation method is as follows: (1) At a temperature of 850℃ and a pressure of 100mbar, H2, TiCl4 and N2 with a purity greater than 99.99% were used to deposit a bonding layer 201 on the surface of the tool substrate 100 by chemical vapor deposition. The deposition time was 120min and the thickness of the bonding layer 201 was 0.5μm. (2) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit the first coating 202 on the surface of the bonding layer 201 by chemical vapor deposition. The deposition time was 60min and the thickness of the first coating 202 was 1.5μm. (3) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a first sub-coating 203 on the surface of the first coating 202 by chemical vapor deposition. The deposition time was 85min and the thickness of the first sub-coating 203 was 2.0μm. At a temperature of 800℃ and a pressure of 5mbar, H2, NbCl4, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a second sub-coating 204 on the surface of the first sub-coating 203 by chemical vapor deposition. The deposition time was 40min and the thickness of 204 was 1.0μm. (4) At a temperature of 800℃ and a pressure of 5mbar, H2, AlCl3, TiCl4, NbCl4 and NH3 with a purity greater than 99.99% were used to deposit a third coating 206 on the surface of the second sub-coating 204 by chemical vapor deposition. The deposition time was 60min and the thickness of the third coating 206 was 1.5μm. (5) At a temperature of 800℃ and a pressure of 50mbar, H2, TiCl4 and NH3 with a purity greater than 99.99% were used to deposit a surface layer 207 on the surface of the third coating 206 by chemical vapor deposition. The deposition time was 90min and the thickness of the surface layer 207 was 1.0μm.
[0089] Comparative Example 1 A composite cutting tool prepared by CVD has two coating layers composed of TiN / TiAlN, and the tool substrate is a WC-Co based cemented carbide. The preparation methods of each layer are as follows: (1) TiN layer, deposition temperature is 900℃, deposition pressure is 100mbar, raw materials are H2, TiCl4 and N2 with purity greater than 99.99%, deposition time is 60min, and the thickness of TiN layer is 1.0μm; (2) Al 0.80 Ti 0.20 The N-layer, using H2, TiCl4, AlCl3, and NH3 with a purity greater than 99.99%, was deposited on the TiN layer surface for 180 min at a deposition temperature of 800℃ and a deposition pressure of 5 mbar. Al... 0.80 Ti 0.20 The thickness of the N layer is 6.5 μm.
[0090] Comparative Example 2 A composite cutting tool prepared by CVD has a coating composition of TiN / MT-Ti(C,N) / TiAlOCN / Al2O3 / TiN, and the tool substrate is a WC-Co based cemented carbide. The preparation methods of each layer are as follows: (1) The first TiN layer is made of H2, TiCl4 and N2 with a purity greater than 99.99%. It is deposited on the surface of the tool substrate for 30 min at a deposition temperature of 900℃ and a deposition pressure of 120mbar. The thickness of the first TiN layer is 0.5μm. (2) MT-Ti(C,N) layer, the raw materials are H2, TiCl4, CH3CN and N2 with a purity greater than 99.99%, deposited on the surface of TiN layer for 90 min at a deposition temperature of 880℃ and a deposition pressure of 5mbar, the thickness of MT-Ti(C,N) layer is 2.0μm; (3) TiAlOCN layer, the raw materials are H2, TiCl4, AlCl3, CO and N2 with a purity greater than 99.99%. Under the conditions of deposition temperature of 950℃ and deposition pressure of 100mbar, the MT-Ti(C,N) layer was deposited for 60min and the thickness of the TiAlOCN layer was 1.0μm. (4) Al2O3 layer: The raw materials are H2, AlCl3, CO2 and H2S with a purity greater than 99.99%. Under the conditions of deposition temperature of 1000℃ and deposition pressure of 80mbar, the Al2O3 layer is deposited on the surface of TiAlOCN layer for 120min and the thickness of Al2O3 layer is 3.0μm. (5) The second TiN layer is made of H2, TiCl4 and N2 with a purity greater than 99.99%. It is deposited on the Al2O3 layer for 40 min at a deposition temperature of 1000℃ and a deposition pressure of 120mbar. The thickness of the second TiN layer is 1.0μm.
[0091] Comparative Example 3 A composite cutting tool prepared by PVD arc ion plating has an AlTiN / TiNbN coating and a WC-Co based cemented carbide substrate. The preparation methods of each layer are as follows: (1) AlTiN layer, the atomic percentage of the target material is Al / Ti=67 / 33, the deposition temperature is 480℃, the pressure control mode is adopted, the deposition pressure is 0.035mbar, the current is 180A, the DC negative bias voltage is -60V, the N2 flow rate is 1500sccm, the workpiece rotation speed is 2rpm, the deposition time is 180min, and the thickness of the AlTiN layer is 4.5μm; (2) TiNbN layer, the atomic percentage of the target material is Ti / Nb=70 / 30, the deposition temperature is 480℃, the pressure control mode is adopted, the deposition pressure is 0.035mbar, the current is 200A, the DC negative bias voltage is -60V, the N2 flow rate is 1500sccm, the workpiece rotation speed is 2rpm, the deposition is carried out on the surface of AlTiN layer for 120min, and the thickness of TiNbN layer is 3.0μm.
[0092] Comparative Example 4 A composite cutting tool prepared by PVD arc ion plating has an AlTiN / AlCrSiN coating and a WC-Co based cemented carbide substrate. The preparation methods of each layer are as follows: (1) AlTiN layer, the atomic percentage of the target material is Al / Ti=67 / 33, the deposition temperature is 480℃, the pressure control mode is adopted, the deposition pressure is 0.035mbar, the current is 200A, the DC negative bias voltage is -60V, the N2 flow rate is 1500sccm, the workpiece rotation speed is 2rpm, the deposition time is 180min, and the thickness of the AlTiN layer is 4.5μm; (2) AlCrSiN layer, the atomic percentage of the target material is Al / Cr / Si=70 / 20 / 10, the deposition temperature is 480℃, the pressure control mode is adopted, the deposition pressure is 0.035mbar, the current is 180A, the DC negative bias voltage is -120V, the N2 flow rate is 1500sccm, the workpiece rotation speed is 2rpm, the AlTiN layer is deposited on the surface for 120min, and the thickness of the AlCrSiN layer is 3.0μm.
[0093] Comparative Example 5 A composite cutting tool prepared by PVD arc ion plating has an AlTiN / AlTiSiN coating and a WC-Co based cemented carbide substrate. The preparation methods of each layer are as follows: (1) AlTiN layer, the atomic percentage of the target material is Al / Ti=67 / 33, the deposition temperature is 480℃, the pressure control mode is adopted, the deposition pressure is 0.035mbar, the current is 200A, the DC negative bias voltage is -60V, the N2 flow rate is 1500sccm, the workpiece rotation speed is 2rpm, the deposition time is 180min, and the thickness of the AlTiN layer is 4.5μm; (2) AlTiSiN layer, the atomic percentage of the target material is Al / Ti / Si=45 / 50 / 5, the deposition temperature is 480℃, the pressure control mode is adopted, the deposition pressure is 0.035mbar, the current is 180A, the DC negative bias voltage is -100V, the N2 flow rate is 1500sccm, the workpiece rotation speed is 2rpm, the AlTiN layer is deposited for 120min, and the thickness of the AlTiSiN layer is 3.0μm.
[0094] Comparative Example 6 A composite cutting tool prepared by CVD, wherein the tool substrate is a WC-Co based cemented carbide and the coating composition is TiN / Al. 0.80 Ti 0.20 N / Ti 0.80 Nb 0.20 N / Al 0.80 Ti 0.12 Nb 0.08 The preparation methods for each layer of N / TiN are as follows: (1) The first TiN layer is made of H2, TiCl4 and N2 with a purity greater than 99.99%. The first TiN layer is deposited on the surface of the tool substrate at a temperature of 850℃ and a pressure of 100mbar for 120min. The thickness of the first TiN layer is 0.5μm. (2) Al 0.80 Ti 0.20 The N-layer is constructed using H2, AlCl3, TiCl4, and NH3 with a purity greater than 99.99%. Al is deposited on the first TiN surface at a temperature of 800℃ and a pressure of 5 mbar. 0.80 Ti 0.20 N layer, deposition time 80 min, Al 0.80 Ti 0.20 The thickness of the N layer is 2.0 μm; (3) Ti 0.80 Nb 0.20 The N-layer uses H2, TiCl4, NbCl4, and NH3 with a purity greater than 99.99% as raw materials. The process is carried out at 800℃ and 10 mbar in Al... 0.80 Ti 0.20 Ni surface deposited Ti 0.80 Nb 0.20 N layer, deposition time 80 min, Ti 0.80 Nb 0.20 The thickness of the N layer is 2.0 μm; (4) Al 0.80 Ti 0.12 Nb 0.08 The N-layer uses H2, AlCl3, TiCl4, NbCl4, and NH3 with a purity greater than 99.99% as raw materials. The process is carried out at a temperature of 800℃ and a pressure of 5 mbar in Ti... 0.80 Nb 0.20 N surface deposition Al 0.80 Ti 0.12 Nb 0.08 N layer, deposition time 80 min, Al 0.80 Ti 0.12 Nb 0.08 The thickness of the N layer is 2.0 μm; (5) The second TiN layer uses H2, TiCl4 and NH3 with a purity greater than 99.99% as raw materials, and is formed at a temperature of 800℃ and a pressure of 50mbar in TAl 0.80 Ti 0.12 Nb 0.08 A second TiN layer was deposited on the surface of the N layer for 60 min, and the thickness of the second TiN layer was 1.0 μm.
[0095] Comparative Example 7 A composite cutting tool prepared by CVD, wherein the tool substrate is a WC-Co based cemented carbide and the coating composition is TiN / Al. 0.80 Ti 0.20 N / Al 0.80 Ti 0.12 Nb 0.08 The preparation methods for each layer of N / TiN are as follows: (1) The first TiN layer is made of H2, TiCl4 and N2 with a purity greater than 99.99%. The first TiN layer is deposited on the surface of the tool substrate at a temperature of 850℃ and a pressure of 100mbar for 120min. The thickness of the first TiN layer is 0.5μm. (2) Al 0.80 Ti 0.20 The N-layer is constructed using H2, AlCl3, TiCl4, and NH3 with a purity greater than 99.99%. Al is deposited on the first TiN surface at a temperature of 800℃ and a pressure of 5 mbar. 0.80 Ti 0.20 N layer, deposition time 120 min, Al 0.80 Ti 0.20 The thickness of the N layer is 3.0 μm; (3) Al 0.80 Ti 0.12 Nb 0.08 The N-layer uses H2, AlCl3, TiCl4, NbCl4, and NH3 with a purity greater than 99.99% as raw materials. The process is carried out at a temperature of 800℃ and a pressure of 5 mbar in Al... 0.80 Ti 0.20 N surface deposition Al 0.80 Ti 0.12 Nb 0.08 N layer, deposition time 120 min, Al 0.80 Ti 0.12 Nb 0.08 The thickness of the N layer is 3.0 μm; (4) The second TiN layer uses H2, TiCl4, and NH3 with a purity greater than 99.99% as raw materials. The mixture is formed at a temperature of 800℃ and a pressure of 50mbar in Al... 0.80 Ti 0.12 Nb 0.08 A second TiN layer was deposited on the surface of the N layer for 60 min, and the thickness of the second TiN layer was 1.0 μm.
[0096] Performance testing: The mechanical properties of Examples 1-7 and Comparative Examples 1-7 of this application were tested.
[0097] (1) The hardness test method of the functional coating is as follows: The surface of the tool substrate is polished to a mirror finish. After the functional coating is deposited, a bearing steel ball with a diameter of 20 mm is used to grind the surface of the functional coating for 20 seconds. Diamond abrasive is added during grinding. Then, the hardness of the coating at the grinding mark is tested using a TTX-NHT2 nanoindenter (Anton Paar GmbH, Austria) (magnified 100 times). The indenter is a diamond Berkovich indenter, with a maximum load of 20 mN, a loading rate of 40 mN / min, an unloading rate of 40 mN / min, and a holding time of 5 seconds. In order to eliminate the influence of the tool substrate on the hardness, the indentation depth is less than 1 / 10 of the total coating thickness. The hardness of 20 different points is measured, and the average value is taken as the hardness of the functional coating.
[0098] (2) The bonding strength test method between the functional coating and the tool substrate is as follows: The bonding strength between the functional coating and the tool substrate is measured using the REVETEST scratch tester manufactured by CSM GmbH, Switzerland. The scratch test method involves sliding a hemispherical diamond indenter with a diameter of approximately 200 micrometers on the surface of the functional coating. During this process, the vertical load L is continuously increased by an automatic loading mechanism. When L reaches its critical load Lc, the test is continued until the critical load Lc is reached. c At this point, the functional coating begins to peel off from the tool substrate, and the critical interfacial load L between the functional coating and the tool substrate... c The minimum load required for the indenter to completely penetrate the functional coating and continuously peel it off from the tool substrate; simultaneously, the frictional force F between the indenter, the functional coating, and the tool substrate changes accordingly. At this point, the functional coating generates acoustic emission. Sensors acquire the acoustic emission signals during the scratching process, the change in load, and the change in tangential force. These signals are amplified, processed, and input into a computer. After A / D conversion, the measurement results are plotted graphically, and the critical load value L is plotted on the acoustic emission signal-load curve. c The corresponding acoustic emission peak is obtained at this point, and the critical load L is at this point. c This serves as the criterion for judging the bonding strength between the functional coating and the tool substrate. The test parameters are: linear loading, load 200N, loading rate 99N / min, scratching speed 5mm / min, and scratch length 5mm.
[0099] (3) The test method for the oxidation weight gain of the functional coating is as follows: The composite tool samples of the above examples and comparative examples with equal mass are placed in a muffle furnace, heated to 900°C in air atmosphere, and held for 60 min. Then the samples are taken out and cooled to room temperature in air. The weight of the samples before and after oxidation is weighed using a high-precision electronic balance with an accuracy of 0.1 mg, and the oxidation weight gain of the samples is calculated.
[0100] Table 1: Mechanical Performance Test Results
[0101] As shown in Table 1, the composite cutting tools prepared in this application have higher bonding strength than the comparative examples. After oxidation at 900℃ for 60 min, the weight gain of the functional coatings is less than that of the comparative examples, and the hardness of the functional coatings is higher than that of the comparative examples.
[0102] The cutting performance of the composite tools prepared in Examples 1-7 and Comparative Examples 1-7 of this application was tested, and the results of the alloy steel milling test are shown in Table 2. The alloy steel cutting performance test was conducted as follows: machining method: milling; workpiece: alloy steel; material: 4140; insert type: APMT1604PDER; cutting conditions: cutting speed 220m / min, feed 0.15mm / z, depth of cut 2.0mm, cutting width ae 40mm, wet cutting, and failure criteria were defined as retardation wear reaching 0.3mm or chipping.
[0103] Table 2: Test Results of Machining Performance of Alloy Steel
[0104] As shown in Table 2, when the composite tool prepared in the embodiments of this application mills 4140 alloy steel, the failure of the composite tool is mainly due to wear, and the service life is higher than that of the comparative example.
[0105] The cutting performance of the composite tools prepared in Examples 1-7 and Comparative Examples 1-7 of this application was tested, and the results of the stainless steel milling test are shown in Table 3. The cutting performance test of stainless steel was conducted as follows: machining method: face milling; workpiece: block part; material: 316L; insert type: APMT1604PDER; cutting conditions: cutting speed 80m / min, feed 0.10mm / z, depth of cut 1.0mm, cutting width ae 40mm, wet cutting, and failure criteria were defined as retardation wear reaching 0.3mm or chipping.
[0106] Table 3: Test Results of Machining Performance of Stainless Steel
[0107] As shown in Table 3, the composite tools prepared in the embodiments of this application have a longer service life than the comparative example when milling 316L stainless steel.
[0108] The composite cutting tools prepared in Examples 1-7 and Comparative Examples 1-7 of this application were used to conduct continuous grooving tests on alloy steel. Failure was defined as the wear on the flank face of the cutting tool reaching 0.3 mm. The test results are shown in Table 4. The continuous grooving test was conducted as follows: machining method: continuous grooving; workpiece: cylindrical part; material: 4140; cutting tool type: ATD420-RM; cutting conditions: cutting speed 180 m / min, feed 0.30 mm, depth of cut 2.0 mm, wet cutting; failure was defined as the wear on the flank face reaching 0.3 mm or the appearance of chipping.
[0109] Table 4: Test Results of Continuous Grooving Test
[0110] As shown in Table 4, the composite cutting tool made of 4140 alloy steel prepared in this application has a longer service life than the comparative example.
[0111] The composite cutting tools prepared in Examples 1-7 and Comparative Examples 1-7 of this application were used to conduct drilling tests on alloy steel. Failure was defined as the wear on the flank face of the cutting tool reaching 0.2 mm. The test results are shown in Table 5. The drilling test was conducted as follows: Machining method: drilling; Workpiece: block; Material: 4140; Cutting tool type: SPMT060204E-DP; Cutting conditions: cutting speed 180 m / min, feed rate 0.08 mm, depth of cut 50 mm, wet cutting.
[0112] Table 5: Test results of drilling tests on alloy steel
[0113] As shown in Table 5, the composite tool prepared in this application has a longer service life than the comparative example when drilling 4140 alloy steel.
[0114] The composite cutting tools prepared in Examples 1-7 and Comparative Examples 1-7 of this application were used to conduct drilling tests on stainless steel 316L. Failure was defined as the wear on the flank face of the cutting tool reaching 0.2 mm. The test results are shown in Table 6. The drilling test procedure for stainless steel 316L was as follows: Machining method: drilling; Workpiece: block; Material: stainless steel 316L; Cutting tool type: SPMT060204E-DP; Cutting conditions: cutting speed 120 m / min, feed rate 0.08 mm, depth of cut 50 mm, wet cutting.
[0115] Table 6: Test results of drilling tests on 316L stainless steel
[0116] As shown in Table 6, the multi-layer coated composite tool prepared by the technical solution of this application has a longer service life than the comparative example when drilling 316L stainless steel.
[0117] In summary, the composite cutting tool of this application possesses high hardness, high wear resistance, high oxidation resistance, high toughness, and higher bonding strength.
[0118] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this invention and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.
[0119] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0120] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0121] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A composite cutting tool, characterized in that, include: A tool substrate and a functional coating disposed on the surface of the tool substrate, the functional coating comprising: A first coating is applied to the surface of the tool substrate; The second coating includes at least one stacked sub-coating, each sub-coating including a first sub-coating and a second sub-coating, the first sub-coating being disposed close to the first coating; A third coating is disposed on the surface of the second sub-coating away from the tool substrate; Wherein, the first coating and the first sub-coating each independently include Al a Ti 1-a N, 0.70≤a≤0.85; The second sub-coating includes Ti 1-x Nb x N, 0.10≤x≤0.30; The third coating includes Al z Ti 1-y-z Nb y N, 0.05≤y≤0.10, 0.70≤z≤0.
85.
2. The composite cutting tool according to claim 1, characterized in that, The number of sub-coatings is 1 to 10.
3. The composite cutting tool according to claim 1, characterized in that, At least one of the following conditions must be met: The first coating is a columnar NaCl-type face-centered cubic crystal structure; The thickness of the first coating is 1μm~3μm; The thickness ratio n of a single first sub-coating and a single second sub-coating satisfies 1 ≤ n ≤ 3; The total thickness of the second coating is 3μm~6μm; The third coating has an equiaxed crystal structure; The thickness of the third coating is 1μm to 3μm.
4. The composite cutting tool according to claim 1, characterized in that, The functional coating further includes a bonding layer disposed between the tool substrate and the first coating.
5. The composite cutting tool according to claim 4, characterized in that, At least one of the following conditions must be met: The bonding layer is made of at least one of TiN and Ti; The thickness of the bonding layer is 0.1 μm to 1.0 μm.
6. The composite cutting tool according to claim 1, characterized in that, The functional coating also includes a surface layer disposed on the surface of the third coating away from the tool substrate.
7. The composite cutting tool according to claim 6, characterized in that, At least one of the following conditions must be met: The surface layer is made of at least one of TiN, TiAlN, NbN, and TiNbN; The thickness of the surface layer is 1.0 μm to 2.0 μm.
8. The composite cutting tool according to claim 1, characterized in that, At least one of the following conditions must be met: The total thickness of the functional coating is 6μm~15μm; The hardness of the functional coating is ≥35 GPa.
9. The composite cutting tool according to claim 1, characterized in that, At least one of the following conditions must be met: The first coating does not contain Nb. Within the first sub-coating, and in a thickness region of 0 nm to 100 nm at a distance from the surface of the first sub-coating to the surface of the second sub-coating, the atomic percentage of Nb is 1 at% to 3 at, based on the total number of Al, Ti, and Nb atoms in the 0 nm to 100 nm thickness region.
10. A method for preparing the composite cutting tool according to any one of claims 1 to 9, characterized in that, include: Provide tool base; The first reaction is carried out in a reaction atmosphere of H2, AlCl3, TiCl4 and NH3 to form a first coating on one side surface of the tool substrate, thereby obtaining a first intermediate product; The second reaction is carried out in a reaction atmosphere of H2, AlCl3, TiCl4, and NH3 to form a first sub-coating on the surface of the first intermediate product, thereby obtaining the second intermediate product. The third reaction is carried out in a reaction atmosphere of H2, TiCl4, NbCl4, and NH3, forming a second sub-coating on the surface of the second intermediate product to obtain the third intermediate product; A fourth reaction is carried out in a reaction atmosphere of H2, AlCl3, TiCl4, NbCl4 and NH3 to form a third coating on the surface of the third intermediate product, thereby obtaining the composite tool; The first sub-coating and the second sub-coating constitute the second coating.
11. The method according to claim 10, characterized in that, The second reaction and the third reaction are carried out alternately m times, where 1 ≤ m ≤ 10 and m is a positive integer.
12. The method according to claim 11, characterized in that, At least one of the following conditions must be met: The temperature of the first reaction is 750℃~850℃; The pressure of the first reaction is 5 mbar to 100 mbar; The first reaction time is 30 min to 90 min; The temperature of the second reaction is 750℃~850℃; The pressure of the second reaction is 5 mbar to 100 mbar; The second reaction time is 6 min to 180 min; The temperature of the third reaction is 750℃~850℃; The pressure of the third reaction is 5 mbar to 100 mbar; The third reaction time is 3 min to 120 min; The temperature of the fourth reaction is 750℃~850℃; The pressure of the fourth reaction is 5 mbar to 100 mbar; The fourth reaction time is 60 min to 180 min.
13. The method according to claim 10, characterized in that, Also includes: A bonding layer is formed on the surface of the tool substrate under the conditions of temperature of 800℃~900℃, pressure of 50mbar~200mbar, and time of 6min~60min.
14. The method according to claim 10, characterized in that, Also includes: A surface layer is formed on the surface of the third coating under conditions of temperature of 750℃~1000℃, pressure of 5mbar~200mbar, and time of 40min~120min.
15. The application of the composite cutting tool according to any one of claims 1 to 9 in milling, grooving and / or drilling of carbon steel, alloy steel and / or stainless steel.